2019
DOI: 10.15406/ijmboa.2019.04.00111
|View full text |Cite
|
Sign up to set email alerts
|

In silico approach for mining of potential drug targets from hypothetical proteins of bacterial proteome

Abstract: An increase in expansion of antibiotic-resistant bacterial pathogens alarms the world's population and creating a wave of the antibiotic apocalypse. The inclination of the death rate due to these antibiotic-resistant superbugs signifies urgency towards a new drug discovery to combat against these bacterial pathogens. The last class of antibiotics developed leaves a huge gap in the antibiotic timeline as the antibiotic development progress failed to kill the bacteria. Current antibiotic targets the central dogm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In a prior study to identify genes associated with macrolide resistance in Streptococcus pneumoniae, we demonstrated a GSEA-approach for gene identification that compared differential gene expression between mRNA expression datasets (41). This study successfully identified known and novel genes though it was limited due to incomplete genome annotation, a common problem for many microbial genomes (42)(43)(44)(45)(46)(47)(48)(49). Applying our GSEA-approach to mRNA expression data derived from a species with a more completely annotated genome, such as human or mouse, our achievable results would improve.…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study to identify genes associated with macrolide resistance in Streptococcus pneumoniae, we demonstrated a GSEA-approach for gene identification that compared differential gene expression between mRNA expression datasets (41). This study successfully identified known and novel genes though it was limited due to incomplete genome annotation, a common problem for many microbial genomes (42)(43)(44)(45)(46)(47)(48)(49). Applying our GSEA-approach to mRNA expression data derived from a species with a more completely annotated genome, such as human or mouse, our achievable results would improve.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies identified drug and vaccine candidates successfully for various bacteria and virus using reverse vaccinology approach (Kumar 2011(Kumar , 2015Kumar and Ramanujam 2020;Omeershffudin and Kumar 2019). In this study, the development of peptide vaccine design has identified by reverse vaccinology, which aims to classify possible candidates for the vaccine considering all the proteome of the virus with the prediction of MHC-I (47 alleles) and MHC-II (27 set alleles) with high antigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many genomes have a substantial number (up to 70%) of hypothetical proteins (HPs), which are ORFs with unknown functions ( Sivashankari and Shanmughavel, 2006 ; Mohan and Venugopal, 2012 ; Bharat Siva Varma et al, 2015 ; Ijaq et al, 2015 ; Islam et al, 2015 ; School et al, 2016 ). Reports estimated that around 33% of National Center for Biotechnology Information (NCBI) knowledgebase sequences in 2006 were HPs ( Kolker et al, 2004 ; Sivashankari and Shanmughavel, 2006 ; Omeershffudin and Kumar, 2019 ). While the exact number of HPs in today’s NCBI is unknown, recent papers on Mycobacterium tuberculosis and Exiguobacterium antarcticum strain B7 genomes report around 27% HPs ( da Costa et al, 2018 ; Yang et al, 2019 ) with 16% HPs in Shigella flexneri ( Gazi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%